Trabalho e adoecimento no município de Toledo, Paraná - Mumbach, Simone Teresa Heck (2017)
The present dissertation aims to understand who are the workers injuried in meat refrigeration work in Toledo, Paraná, what is their labor trajectory, how was constituted the relationship between the production process and the emergence of injuried or work acidents and how its aggravation occurred, in order to think about how the sick workes experience and life the “being sick”. In this sense, we reported the transformations generated in their daily life and how their social relations were affected. Finally, we problematized how the process occurs when possible, of reinsertion of this worker, affected by pain and suffering, caused by degrading processes of meat production, in the productive process. The research comes to life from semistructured interviews contucted with 14 workers injuried in prodution processes of FRIG, showing the deep “marks” that the processes of meat production left in their bodies and in their minds.